Sleep of preschoolers during the coronavirus disease 2019 (COVID‐19) outbreak - Liu, Zhijun; Tang, Hui; Jin, Qiyun; Wang, Guanghai; Yang, Zixin; Chen, Hongyan; Yan, Hongxia; Rao, Wenjie; Owens, Judith (Journal of sleep research, 2021)
Coronavirus disease 2019 (COVID‐19) has resulted in a significantly large number of psychological consequences, including sleep health. The present study evaluated sleep patterns, sleep disturbances, and associated factors in Chinese preschoolers confined at home during the COVID‐19 outbreak. Caregivers of 1619 preschoolers (aged 4–6 years) recruited from 11 preschools in Zunyi, Guizhou province completed the Children’s Sleep Habit Questionnaire (CSHQ) between 17th and 19th February 2020. Data were compared to a sociodemographically similar sample of preschoolers (included in the 11 preschools) in 2018. Compared to the 2018 sample, the confined preschoolers demonstrated changes in sleep patterns characterized by later bedtimes and wake times, longer nocturnal and shorter nap sleep durations, comparable 24‐hr sleep duration, and fewer caregiver‐reported sleep disturbances. Moreover, behavioural practices (sleeping arrangement, reduced electronic device use, regular diet) and parenting practices (harmonious family atmosphere and increased parent‐child communication) were associated with less sleep disturbances in the confined sample. The present study provides the first description of the impact of prolonged home confinement during the COVID‐19 outbreak on sleep patterns and sleep disturbances in preschoolers, as well as highlighting the importance of the link between sleep health and family factors. Given that disrupted and insufficient sleep has been linked to immune system dysfunction, our findings also have potential implications for resilience to infection in young children during the COVID‐19 pandemic. Future studies should further explore deficient sleep as a risk factor for coronavirus infection.